Management of Traumatic Brain Injury: A review Update (Journal of Shaheed Suhrawardy Medical College, 2017)
Traumatic Brain Injury leads to serious consequences. Approximately half of all deaths is related to traumatic injury and the main cause of head trauma. Extradural haematomas (EDH) develops in all major head injuries. A head injury patient who is only temporary loss of consciousness and is left asleep may sometimes be found dead in the bed next morning due to extradural haematoma. Extradural haematoma which lies in between the inner surface of skull and stripes of dural membrane, are nearly always caused by, and located near a skull fracture. The collection takes several forms in terms of size, location, speed of development and effects they exert on patient. Immediate management is necessary to decrease the bad consequences. In this review the management of traumatic brain injury is highlighted.J Shaheed Suhrawardy Med Coll, 2014; 6(2):87-89